Synthesis and Charcterization of Some Cold Brand Reactive Dyes and Their Application on Various Fibres - Patel, Y.S.; Patel, K.C.; Patel, S.K. (Asian Journal of Chemistry, 2010)
Various reactive dyes have been prepared by coupling diazotised 4,4'-methylene-bis-o-bromo aniline with cyanurated coupling components and their dyeing performance as reactive dyes has been assessed on silk, wool and cotton fibre. All the dyes gave yellow to maroon shades with good to very good light fastness on each fibre. The purity of dyes was checked by thin layer chromatography. The IR spectra showed all characteristic bands and a representative dye's PMR spectra showed all the signals. The percentage dye-bath exhaustion on different fibres was reasonably good and acceptable. The dyed fibres showed moderate to very good fastness to light, washing and rubbing.